2017
DOI: 10.1186/s40814-017-0161-8
|View full text |Cite|
|
Sign up to set email alerts
|

A feasibility study of the Mini-AFTER telephone intervention for the management of fear of recurrence in breast cancer survivors: a mixed-methods study protocol

Abstract: BackgroundFear of recurrence (FoR) is a major concern for patients following treatment for primary breast cancer, affecting 60–99% of breast cancer survivors. Mini-AFTER is a brief intervention developed to address this fear, that breast care nurses are ideally placed to deliver. However, their interest in delivering such an intervention is unknown and crucial to its introduction. This study aims to assess the perceived feasibility of the Mini-AFTER telephone intervention for implementation by breast care nurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“… a Confidence interval around point estimate ranges 5 units (bootstrap) b Confidence interval around point estimate ranges 8 units (bootstrap) 1 From Concern about Recurrence Scale [ 32 ] 2 From Fears of Cancer Recurrence Inventory [ 27 ] 3 From Worry of Cancer Scale [ 34 ] 4 From FORPSYCH study [ 35 ] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… a Confidence interval around point estimate ranges 5 units (bootstrap) b Confidence interval around point estimate ranges 8 units (bootstrap) 1 From Concern about Recurrence Scale [ 32 ] 2 From Fears of Cancer Recurrence Inventory [ 27 ] 3 From Worry of Cancer Scale [ 34 ] 4 From FORPSYCH study [ 35 ] …”
Section: Resultsmentioning
confidence: 99%
“…A recent comment has highlighted that some assessments of FCR are clearly designed to assess intensity of fear such as the FCRI-Severity subscale (9 items), whereas the CAR-Q includes 3 aspects of clinical symptoms that Lebel et al [ 33 ] have argued are indicative of clinical levels of FCR [ 34 ]. Our position would be that the FCR4 is a quick screen for fear itself of FCR, whereas the FCR7 would function as a possible indicator of 3 of the clinical issues recommended for assessment that could trigger early intervention [ 35 ]. We would encourage additional item development if the researcher / clinician wished to adopt a measure to locate clinical FCR.…”
Section: Discussionmentioning
confidence: 99%
“…They can do so through direct intervention or through referral to a suitable psychological service. Several studies (47)(48)(49) found that intervention by an oncological nurse (47,48) had a positive effect on survivors and reduced their levels of anxiety. Intervention that encourages survivors to participate in meaningful and useful activities (such as contributing to the community) may also be effective in helping survivors cope with the fear of breast cancer recurrence (11).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, within the context of psychosocial care of cancer patients, detecting these fears (either through PCI or by simply asking about them) needs to be coupled with the provision of further support and therapeutic assistance by psycho‐oncology services, if required. Patients with moderate to extensive FCR levels need to receive patient‐centred support or intervention that is commensurate with their clinical presentation (Cruickshank et al., ). A previous report has highlighted this difficulty for cancer treatment services: There is reticence to invite discussion about psychological problems associated with the diagnosis, treatment and follow‐up care because of lack of training, poor methods of screening and minimal provision of referral centres for specialist services (Absolom et al., ).…”
Section: Discussionmentioning
confidence: 99%